The development and standardization of the St. Paul University high school admission test (SPU-HSAT) - Gonzales, Richard de la Cruz (Animo Repository, 1987)
This study develops and standardizes a high school admission Test (HSAT) for St. Paul University High School. The HSAT will be used as an admission test for first year applicants of SPU-High School. The processes involved in the development are as follows: 1) planning the test specifications and objectives 2) item writing and reviewing 3) assembly of the pretest forms 4) pretest administration 5) pretest item analysis 6) assembly of the final form 7) administering the final form 8) establishment of test reliability 9) establishment of test validity and 10) establishment of norms and score scales. The findings of the study were: 1. The pretest data yielded that the HSAT have a difficulty level (p) ranging from very easy (.95) to very difficult (.06). Majority of the items (72 percent) were moderately difficult. The Numerical subtest was found to be easiest while Grammar subtest seemed to be difficult. The whole test has a mean difficulty of .52 and a standard deviation of .22 2. The pretest forms discrimination index (rbis) was found out to be ranging from -.32 to .82. Two hundred seven items or 58 percent were found to have high discrimination indices. The overall mean discrimination is .41 with a standard deviation of .20. Numerical subtest has the highest mean discrimination (.47) while Grammar has the lowest mean discrimination (.31) 3. From the option analysis, majority of the items (65 percent) satisfied the set of criteria for item acceptability 4. The difficulty level (p) of the final form of the HSAT ranges from .10 to .90 with a mean of .55 and a standard deviation of .14. The reasoning ability subtest is the easiest while Grammar subtest is the most difficult 5. The discrimination index (rbis) of the final form of the HSAT ranges from .30 to .74 with a mean of .49 and a standard deviation of .11. The numerical subtest was found to be highly discriminating while the Reading Comprehension subtest to be least discriminating. 6. The interitem test reliability using the KR#2